PENGARUH KUALITAS PELAYANAN TERHADAP MINAT MENABUNG ANGGOTA DI CU MURA KOPA BALAI KARANGAN: PENGARUH KUALITAS PELAYANAN TERHADAP MINAT MENABUNG ANGGOTA DI CU MURA KOPA BALAI KARANGAN - Dina Octaviani; Margareta Mery (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
This study was conducted with the aim of knowing the effect of service quality on the interest in saving members at CU Mura Kopa Balai Karangan. This research is quantitative descriptive. The data collection technique used was in the form of a questionnaire distributed online. The sample selected was 94 respondents based on the slovin formula. The research method used is simple linear regression analysis. The results obtained through a simple linear regression test show that Physical Evidence (Tangibles), Reliability (Reliability), Responsiveness (Responsiveness), Assurance (Assurance), and Empathy (Emphaty) have a significant effect on the interest in saving Credit Union members Mura Kopa Balai Karangan . Members' responses to the service quality of CU Mura Kopa provided by CU Mura Kopa Balai Karangan, based on the overall results of the questions answered by respondents, it can be said that the quality of service strongly agrees through the average score of respondents' answers. The simple linear regression test of service quality which consists of assurance, reliability, tangible, empathy and responsiveness together has a significant effect on saving interest of members of Mura Kopa Balai Karangan Credit Union by 55.5%.